Isomeric C12-Alkamides from the Roots of Echinacea purpurea Improve Basal and Insulin-Dependent Glucose Uptake in 3T3-L1 Adipocytes - Kotowska, Dorota; El-Houri, Rime B.; Borkowski, Kamil; Petersen, Rasmus K.; Fretté, Xavier C.; Wolber, Gerhard; Grevsen, Kai; Christensen, Kathrine B.; Christensen, Lars P.; Kristiansen, Karsten (Planta Medica, 2014)
Echinacea purpurea has been used in traditional medicine as a remedy for the treatment and prevention of upper respiratory tract infections and the common cold. Recent investigations have indicated that E. purpurea also has an effect on insulin resistance. A dichloromethane extract of E. purpurea roots was found to enhance glucose uptake in adipocytes and to activate peroxisome proliferator-activated receptor γ. The purpose of the present study was to identify the bioactive compounds responsible for the potential antidiabetic effect of the dichloromethane extract using a bioassay-guided fractionation approach. Basal and insulin-dependent glucose uptake in 3T3-L1 adipocytes were used to assess the bioactivity of extract, fractions and isolated metabolites. A peroxisome proliferator-activated receptor γ transactivation assay was used to determine the peroxisome proliferator-activated receptor γ activating properties of the extract, active fractions and isolated metabolites. Two novel isomeric dodeca-2E,4E,8Z,10E/Z-tetraenoic acid 2-methylbutylamides together with two known C12-alkamides and α-linolenic acid were isolated from the active fractions. The isomeric C12-alkamides were found to activate peroxisome proliferator-activated receptor γ, to increase basal and insulin-dependent glucose uptake in adipocytes in a dose-dependent manner, and to exhibit characteristics of a peroxisome proliferator-activated receptor γ partial agonist.
Keywords: Echinacea purpurea; Asteraceae; alkamides; adipocytes; glucose uptake; PPARγ partial agonist